Towards understanding the mechanism of dimerisation of Saccharomyces cerevisiae eukaryotic translation initiation factor 5A - Gentz, Petra Monika (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2008)
Eukaryotic translation initiation factor 5A (eIF5A) is the only known protein to contain hypusine, formed by post-translational modification of a highly conserved lysine residue. Hypusination is essential for eIF5A function, being required for binding of a specific subset of mRNAs necessary for progression of eukaryotic cells through the G1-S checkpoint. Little structural information is available for eIF5A other than that derived from archaeal homologues. The aim of this study was to conduct structure-function studies on Saccharomyces cerevisiae (yeast) eIF5A, encoded by TIF51A. Homology models of eIF5A were generated from the Methanococcus jannaschii archaeal homologue (aIF5A) and two Leishmania eIF5As. The models, along with secondary structure predictions identified an a-helix on the C-terminal domain, unique to eukaryote eIF5A. The Neurospora crassa structural analogue, HEX-1, which dimerises in three configurations, was used to generate similar dimeric model configurations of eIF5A. A biochemical and functional analysis was used to validate the homology models of eIF5A.Since the crystal structures of aIF5A and eIF5A were solved from unhypusinated protein produced in Escherichia coli, 6 x His-tagged eIF5A (His-eIF5A) was used for biochemical analysis. This analysis revealed that eIF5A existed as a dimer in solution, dependent on the presence of the highly conserved Cys 39 residue. A yeast TIF51A/TIF51B null yeast strain, with a chromosomal copy of TIF51A under control of PGAL1, was used to confirm that HiseIF5A and selected eIF5A mutants were functional in vivo. Biochemical analysis showed that hypusinated His-eIF5A also exists as a dimer, but neither the dimerisation, nor the function of eIF5A are dependent on the presence of Cys 39. Rather they depend on the presence of hypusine (Hpu) 51 and the presence of RNA leading to the conclusion that RNA and hypusine are required for dimerisation and hence function, of native eIF5A in vivo. In contrast, a Lys 51 to Arg 51 substitution or RNase treatment of His-eIF5A produced in E. coli did not destabilize the dimeric form, suggesting different folding/dimerisation mechanisms in E. coli and yeast cells. The information obtained from the initial homology models, together with the results of the biochemical analysis was used to propose a mechanism for dimerisation of yeast eIF5A involving both hypusine and RNA.
Keywords: Cytology; Molecular biology; Biochemistry; Proteins -- Analysis; Proteomics; Polypeptides; Amino acids -- Synthesis